Correlation Between Right Ventricular Function Using Myocardial Performance Index (Tei Index) with Pulmonary Arterial Hypertension Severity in Patient with Atrial Septal Defect - Hendry Purnasidha Bagaswoto; Dyah Wulan Anggrahini; Hasanah Mumpuni; Lucia Krisdinarti (ACI (Acta Cardiologia Indonesiana), 2016)
Background: Right ventricular (RV) volume overload that occurs in patients with atrial septal defect (ASD) could lead to the development of pulmonary arterial hypertension (PAH). RV function has been found depressed in some patients with PAH. Myocardial performance index (MPI) is one of methods to assess RV function. The aim of this study was to assess correlation between RVfunction using RV-MPI with PAH severity in patients with ASD. Methods: We conducted a cross sectional study between July 2012-July 2013. We enrolled 67patients with secundum type ASD. RV-MPI, defi ned as the sum of isovolumic relaxation time and isovolumic contraction time derived by ejection time, was measured from tricuspid infl ow and RV outflow. The normal range is 0.28-0.32. Pulmonary artery systolic pressure (PASP) was measured from echocardiography. Results: There were 67 patients (54 women) with mean age was 38.01±14.29 years (11.9% with no PAH, 11.9% mild PAH, 26.9% moderate PAH and 49.3% severe PAH). The mean PASP was 67.16±32.33 mmHg and mean MPI was 0.44±0.25. We found signifi cant correlation between PASP and MPI (r=0.73; p=0.000). In addition, we classifi ed the PAH severity based on PASP and there was signifi cant differences of MPI between groups (no PAH, MPI 0.25±0.07; mild PAH 0.24±0.05; moderate PAH 0.24±0.12; severe PAH 0.63±0.21; p=0.000). Furthermore, in severe PAH group, the correlation between PASP and MPI remain signifi cant (r=0.42; p<0.05). Conclusion: These result demonstrate a correlation between PAH severity and MPI in patientswith ASD. Specifi cally, RV function found decreased in ASD patients with severe PAH.Keyword: myocardial performance index (Tei index), pulmonary arterial hypertension, right ventricular function, atrial septal defect